Latent factors of elementary school students' self-control in online learning - Kurniawan, Dedy; Alghadari, Fiki (S&Co Publishing, 2023)
Online learning during the pandemic has been a contributing factor to learning loss. However, for students who possess self-control, their learning outcomes still fall within the good category. This research aims to analyze the latent factors of self-control among elementary school students in the context of online learning. This study applied coding analysis, exploratory and confirmatory factor analysis. It involves 6th-grade students (N=24) purposively selected from one elementary school in the Tanjungpandan district for the coding analysis study, resulting in 84 responses that formed 16 codes for designing the students' self-control instrument model. Additionally, 4th to 6th-grade elementary school students (N=146) from four districts in Belitung, Bangka Belitung, Indonesia were randomly selected for the factor analysis study to construct latent factors based on the 16 formed codes. The data for the coding analysis and factor analysis were collected through online surveys. The coding analysis survey used open-ended questions, while the factor analysis survey used items designed on a Likert scale with a response model based on the degree of